Synthesis, characterization and thermal behaviour of solid 2-methoxybenzoates of trivalent metals - Siqueira, A. B. [UNESP]; Carvalho, C. T. [UNESP]; Ionashiro, E. Y.; Bannach, Gilbert [UNESP]; Rodrigues, E. C.; Ionashiro, Massao [UNESP] (Springer, 2008)
Solid-state Ln(L)(3) compounds, where Ln stands for trivalent Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu and Y and L is 2-methoxybenzoate have been synthesized. Simultaneous thermogravimetry and differential thermal analysis (TG-DTA), differential scanning calorimetry (DSC), X-ray powder diffractometry, infrared spectroscopy and complexometry were used to characterize and to study the thermal behaviour of these compounds. The results provided information on the composition, dehydration, coordination mode, structure, thermal behaviour and thermal decomposition.
Keywords: characterization; heavier lanthanides; 2-methoxybenzoate; thermal behaviour